2022
DOI: 10.26603/001c.35722
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Shoulder Test Differences Exist Bilaterally in Healthy Pitchers

Abstract: Background There is a lack of valid and reliable tests that assess upper extremity strength and function for rehabilitation and injury prevention purposes in throwing athletes. The Athletic Shoulder (ASH) test has been proposed as a reliable measure of shoulder strength, but has not yet been studied in baseball pitchers. Hypothesis/Purpose The purpose of this study was to establish values for healthy baseball pitchers performing the ASH test, compare those values with other common tests of shoulder strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…It is thought the repetitive throwing motion results in muscular weakness and atrophy of the infraspinatus, potentially mediated by nerve impingement and infrequent external rotation motion [ 41 , 42 ]. Interestingly, the shoulder strength values derived from the ASH test in the current study are higher than those previously reported in NCAA Division II baseball players, for both throwing and non-throwing arm and across all arm positions [ 15 ].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…It is thought the repetitive throwing motion results in muscular weakness and atrophy of the infraspinatus, potentially mediated by nerve impingement and infrequent external rotation motion [ 41 , 42 ]. Interestingly, the shoulder strength values derived from the ASH test in the current study are higher than those previously reported in NCAA Division II baseball players, for both throwing and non-throwing arm and across all arm positions [ 15 ].…”
Section: Discussioncontrasting
confidence: 73%
“…As such, strengthening the external rotator and internal rotator musculature of the shoulder has been identified as a promising injury-risk reduction strategy [ 2 , 10 , 11 ]. Recently, the athletic shoulder test was found to demonstrate an excellent interday reliability net peak force (ICC 0.94–0.98) and high absolute reliability values (standard error of measurement: 4.8–10.8), lending itself to serve as a valid tool for isometrically evaluating shoulder strength in athletes [ 14 ], particularly in baseball players [ 15 ]. This assessment offers a non-invasive field-based technique to evaluate the changes in shoulder strength for throwing performance and helps to identify potential risk factors for injuries, without the need for costly laboratory equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In light of these conflicting views on classifications, there is also evidence supporting scapular dyskinesis as being a normal finding in both symptomatic and asymptomatic overhead athletes or even that it may be a beneficial adaptation to increase velocity through force coupling and/or length-tension relationships for force generating muscles with overhead hitting or throwing. 11,12 The purpose of this case report is to highlight the examination and treatment of a youth softball pitcher referred to physical therapy with the diagnosis of scapular dyskinesis. Key components of the examination, including WSP pathomechanics, will be presented and discussed; along with the relevance of scapular dyskinesis in this case.…”
Section: Introductionmentioning
confidence: 99%